High internal quantum efficiency ZnO/ZnMgO multiple quantum wells prepared on GaN/sapphire templates for ultraviolet light emitting diodes. Issue 22 (29th May 2019) - Chen, Shanshan; Xu, Chenxiao; Pan, Xinhua; He, Haiping; Huang, Jingyun; Lu, Bin; Ye, Zhizhen
Abstract : Dramatically reduced edge threading dislocations and a record IQE of 61% are obtained for ZnO/Zn0.9 Mg0.1 O MQWs by using GaN/Al2 O3 as substrates. Abstract : 5-Period ZnO/Zn0.9 Mg0.1 O Multiple Quantum Wells (MQWs) were fabricated by plasma-assisted molecular beam epitaxy. The dominant edge threading dislocations in epitaxial films were dramatically reduced by using GaN/Al2 O3 as substrates. As a result, a record high internal quantum efficiency of 61% at 300 K was obtained for the ZnO/Zn0.9 Mg0.1 O MQWs.